The Development of V2 Playmat Game to Increase Movement Skill Children with Intellectual Disability (ID) - Selvi Atesya Kesumawati Selvi Atesya Kesumawati; Bayu Hardiyono Bayu Hardiyono; Vinny Marselly; Husni Fahritsani Husni Fahritsani (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Children with mild ID are also referred to as debilitating or able to educate. Children with a mild ID can receive education like other normal children. Most of the Children with mild ID experience delays in physical development that have an impact on basic movement skills problems such as locomotor movements of running, jumping and jumping, as well as manipulative throwing and catching an object. The purpose of this study is to develop a learning model through V2 playmat games which are designed and developed to stimulate basic movement skills in children with mild ID in the Adaptive Physical Education learning process. The subjects of this study were children with mild ID aged 8-12 years totaling 10 people in the narrow-scale trial and 25 people in the wide-scale trial. Involving 3 experts consisting of learning media experts, learning material experts and Physical Education practitioners. The method used in this research is the Lee and Owens Analysis, Design, Development Implementation, and Evaluation (ADDIE) research and development method. The results of the validation test by experts using the Content Validity Index (CVI) and Content Validity Ratio (CVR) tests which show an average CVR value of 0.27 in other words the Playmatt game model developed is appropriate or relevant, or good and also has high content validity. in improving basic movement skills, cognitive, and mild ATG pleasure.